Evaluation of a dual-PPG system for pulse transit time monitoring - Lubin, M.; Gerbelot, R.; Prada, R.; Porcherot, J.; Bonnet, S. (2021 43rd Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC), 2021)
This work presents a new dual-photoplethysmographic (PPG) system for pulse transit time (PTT) monitoring. An experiment has been set up in order to compare the PTT measurement between carotid and radial arteries from two systems: our physiological multimodal platform (PMP) and the Complior® tonometer. This work explores the comparison between such optical and mechanical modalities. The results show that the PPG device tends to overestimate the PTT (RMSE = 16 ms). Furthermore, both mechanical and optical signals have been superposed and demonstrated that pulse morphologies are quite similar.Clinical Relevance-Carotid-radial pulse wave velocity (PWV) is compared on a small cohort of subjects and significant differences are observed between optical and mechanical-based systems.